SHAPING SUSTAINABLE TRANSPORTATION: A BIBLIOMETRIC EXPLORATION OF LEADING RESEARCH IN ELECTRIC VEHICLES ADOPTION - Rosmaizul Mustapha; Ahmad Nazrul Hakimi Ibrahim; Muhamad Nazri Borhan, (Jurnal Kejuruteraan, Teknologi and Sains Sosial (JKTSS), 2025)
The adoption of Electric Vehicles (EVs) has become a central topic in sustainable transportation research, driven by global environmental concerns, regulatory initiatives, and technological advancements. Understanding the most influential contributions in this area is essential to guide future research directions and policy development. This study applies a bibliometric approach using the Scopus database, retrieving articles from the title field with the keywords (“EV adoption” OR “EVs adoption” OR “electric vehicle adoption” OR “electric vehicles adoption”). The search covered publications from 2009 to 2025, yielding 657 records eligible for bibliometric analysis. Bibliomagica 2.9 was used to extract descriptive data, while VOSviewer generated and visualized citation networks and overlay maps. The 20 most cited publications were identified and examined by author, title, source, citation count, and citations per year. Citation frequencies ranged between 158 and 1,237, with an average of 400.4 citations. The most cited study by Egbue and Long (2012) emphasized psychological barriers to EV adoption, followed by works by Sierzchula et al. (2014) on financial incentives and Rezvani et al. (2015) on consumer behavior. Results show that EV adoption research predominantly focuses on consumer attitudes, government incentives, and sociodemographic factors. Overlay visualizations reveal increasing citations for recent studies, highlighting evolving scholarly priorities and the need to address regional disparities and socio-technical challenges.